E-Commerce User Interface Enhancement Based on User Experience Evaluation of Usability Aspects - I Nyoman Wahyu Semeru Putra; I Made Candiasa; I Gede Aris Gunadi (Institute of Computer Science (IOCS), 2023)
The growth of information technology has had an impact on the business sector, as seen by the proliferation of purchasing and selling sites (e-commerce) that have made it easier for individuals to buy and sell things. In order to achieve the goal of improving user experience on e-commerce websites, this research analyzes user experience on e-commerce websites so that Rumah58.com can be known by a larger portion of the community and can provide recommendations for website improvements for Rumah58.com that are tailored to the results of user experience analysis. The research yields recommendations for enhancing the Rumah58.com e-commerce website in order to increase its users' comfort and pleasure. It is intended that the Rumah58.com e-commerce website may give even greater ease and satisfaction for its users, as the website is now easier to access, the navigation is intuitive, and the website's features are comprehensive and clear. Visitors have faster access to the Rumah58.com website, the navigation is intuitive, and the website's features are comprehensive and comprehensible.